2012
DOI: 10.1073/pnas.1208141109
|View full text |Cite
|
Sign up to set email alerts
|

Serum Response Factor (SRF)-cofilin-actin signaling axis modulates mitochondrial dynamics

Abstract: Aberrant mitochondrial function, morphology, and transport are main features of neurodegenerative diseases. To date, mitochondrial transport within neurons is thought to rely mainly on microtubules, whereas actin might mediate short-range movements and mitochondrial anchoring. Here, we analyzed the impact of actin on neuronal mitochondrial size and localization. F-actin enhanced mitochondrial size and mitochondrial number in neurites and growth cones. In contrast, raising G-actin resulted in mitochondrial frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 52 publications
4
39
0
Order By: Relevance
“…Recent evidence revealed that cofilin and Drp1 play critical roles in regulation of mitochondrial function by translocating from the cytosol to mitochondria [14, 17, 2628]. We next investigated whether mitochondrial translocation of cofilin and Drp1 is necessary for erucin to induce mitochondrial fission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence revealed that cofilin and Drp1 play critical roles in regulation of mitochondrial function by translocating from the cytosol to mitochondria [14, 17, 2628]. We next investigated whether mitochondrial translocation of cofilin and Drp1 is necessary for erucin to induce mitochondrial fission.…”
Section: Resultsmentioning
confidence: 99%
“…Cofilin functions as a biosensor that integrates cytoskeletal regulation with mitochondrial function. The results of another study indicated that under certain cellular conditions cofilin might directly or indirectly associate with mitochondria and modulate mitochondrial functions [14]. However, the mechanism by which cofilin affects mitochondrial dynamics and functions, and is responsible for mitochondrial apoptosis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Because mammals contain homologs of each of these in the form of multiple genes and/or splice variants, it is possible that these factors are involved in mitochondrial fission. Indeed, there is some evidence that cofilin participates in mitochondrial dynamics in neurons (Beck et al, 2012).…”
Section: Budding Yeastmentioning
confidence: 99%
“…SRF, a member of the highly conserved MADS box family of transcription factors, has been shown to regulate several genes involved in cell growth [23] , migration [38] , cytoskeletal organization [39] , energy metabolism [40] and myogenesis [41] . The necessity of SRF for embryogenesis and early development has been reported [42] , whereas in adults low levels of SRF have been shown to be beneficial [43] .…”
Section: Up-regulated Genes Down-regulated Genesmentioning
confidence: 99%